ПРИВРЕДНИ КРИМИНАЛИТЕТ У РЕПУБЛИЦИ СРБИЈИ У ПЕРИОДУ ОД 2006. ДО 2015. ГОДИНЕ - Cvetković, Dragan M; Jovanović, Zoran ž; Bešić, Davor (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
ECONOMIC CRIME IN SERBIA IN THE PERIOD FROM 2006 TO 2015 Abstract Economic crime is undoubtedly one of the most actual problems of our day, which as a special form of crime increasingly undermines the smooth functioning of the economy, but also causes considerable material damage to the company. Data on economic crimes, and especially the material consequences caused by taking into account the dark figure of this criminal phenomenon, leaving a disturbing impression. The consequences of economic crime on society are manifold: direct damage to businesses, state budget, total industrial and economic developments and the country as a whole. It is therefore of utmost importance to look at the proper statistics for this criminal phenomenon, ie. the structure of behavior that manifests itself through economic crime, followed by changes in its scope and manifestations of economic crime. In this paper, we define the concept and characteristics of economic crime. We will show the participation of economic crime in the mass of the entire crime, dynamics and structure of economic crime. We will try to isolate the movement and show the most common criminal acts of economic crime in the Republic of Serbia in the period 2006 -2015. year, for the sake of adequate involvement of the competent authorities in order to prevent this type of crime. Key words: Economic crime, consequences, dark figure, criminal offenses.